Slidesgo Assisted Interactive Media Development to Enhance Motivation in Technology Learning for Fifth Grade Students in Elementary school - Nuriyah Salsyabila; Zulherman Zulherman (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The lack of motivation to learn of students can make the learning process in grade V of elementary school hampered. Low motivation to learn can be seen from the lack of enthusiasm from students and quickly feeling bored when learning in class and the learning media used by teachers are considered uninteresting or monotonous. Methodology: The method used in this study is Research and Development (RnD) with the ADDIE (Analyse, Design, Development, Implementational, Evaluation) model. This research was conducted at 3 elementary school such as SDN Balimester 01 AM, SDN Balimester 06 AM and SDN Rawa Bunga 11 AM. Results: The results of the assessment obtained from the Expert Lecturers include: 1) Media experts give a validation assessment of 72 % or "Feasible", 2) Subject matter experts give a validation assessment of 84 % or "Very Feasible", and 3) Linguists give a validation assessment of 70 % or "Feasible". The results of the use of media in increasing learning motivation were also seen in students in the small group test with data of 86.24 % (Sd Bm 01 am) and the large group test with data obtained of 89.30 % (Sd Bm 06 Morning) and 90.37 % (Sd Rb 11 Morning). Thus, it can be concluded that Interactive Media assisted by the Slidesgo Platform is very suitable for use as a learning medium that can also increase students' motivation to learn. Contribution: this study shwon that the Slidesgo platform has a significant impact on increasing the learning motivation of fifth-grade elementary school students